Project Management Innovations Driving Subsidiary Reputation: A Defence Industry Case Study - Marco Antonio AMARAL FERIS; Klaus Peter STOLZMANN; Rodney J. CLARKE (Communications of International Proceedings, 2020)
This qualitative study examines the development of an innovative military electronic board by a subsidiary of a high-tech multinational company (MNC). The module involved software, hardware and mechanical projects. A conflict with a traditional supplier of avionics systems in a project phase where scope changes are not permitted to vary, necessitated a change in the management approach. There were considerable technical, psychological and political challenges involved in the development of this module. This paper describes the unorthodox application of Agile methods that enabled this project to be delivered within much shorter timeframes than similar products developed by the headquarters. As a consequence of successfully completing this project, the role of the subsidiary in relation to the headquarters changed substantially. The level of confidence in the subsidiary’s technical capacity increased and it now has almost a complete control of the NPD cycles for all national projects.
Keywords: Project Management; NPD; Springboard Theory; Stakeholder Analysis; Defence.